2015
DOI: 10.1016/j.taap.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Flavanone silibinin treatment attenuates nitrogen mustard-induced toxic effects in mouse skin

Abstract: Currently, there is no effective antidote to prevent skin injuries by sulfur mustard (SM) and nitrogen mustard (NM), which are vesicating agents with potential relevance to chemical warfare, terrorist attacks, or industrial/laboratory accidents. Our earlier report has demonstrated the therapeutic efficacy of silibinin, a natural flavanone, in reversing monofunctional alkylating SM analog 2-chloroethyl ethyl sulfide-induced toxic effects in mouse skin. To translate this effect to a bifunctional alkylating vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Phosphorylation of the histone H2A variant, H2A.X, which recruits DNA damage response proteins, is critical for the repair of DNA breaks (Mah et al, 2010; Scully and Xie, 2013). Consistent with previous findings (Inturi et al, 2014; Jain et al, 2015; Joseph et al, 2011), we found that NM caused a rapid increase in phospho H2A.X in the nuclei of basal and suprabasal cells of the interfollicular epidermis and the outer root sheath of hair follicles, presumably a response to DNA damage. Two-three days post-NM, phospho-H2A.X was also evident in infiltrating neutrophils and macrophages, which are known to undergo apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…Phosphorylation of the histone H2A variant, H2A.X, which recruits DNA damage response proteins, is critical for the repair of DNA breaks (Mah et al, 2010; Scully and Xie, 2013). Consistent with previous findings (Inturi et al, 2014; Jain et al, 2015; Joseph et al, 2011), we found that NM caused a rapid increase in phospho H2A.X in the nuclei of basal and suprabasal cells of the interfollicular epidermis and the outer root sheath of hair follicles, presumably a response to DNA damage. Two-three days post-NM, phospho-H2A.X was also evident in infiltrating neutrophils and macrophages, which are known to undergo apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…Mustard gas exposure affects various organs including lungs, bone marrow and skin leading to early and late manifestations of morbidity 2,5,12,13 . If left untreated, mustard induced skin injury is characterized by erythema and edema that progresses to vesication of the skin resulting in epidermal separation, vacuolization and epidermal necrosis 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous exposure to SM triggers acute inflammatory lesions in the skin and in incidents of massive exposure, death 4 . Nitrogen mustard (NM), an analog of SM, has been used as a laboratory surrogate to develop animal models of cutaneous toxicity 5,6 . Although the DNA alkylating properties of NM have utility in a clinical setting for topical chemotherapy and treatment of cutaneous T cell lymphoma, such treatments have been associated with side effects that include cutaneous inflammation 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Silibinin (Figure 3G) is a natural product flavanone extract of the milk thistle plant[97]. It is commonly sold as a dietary supplement for treatment of hepatotoxicity but is also taken for a diverse range of ailments.…”
Section: 0 Potential Antioxidant Therapies: Mechanisms Efficacy Amentioning
confidence: 99%
“…Silibinin has been studied for its utility against oxidative stress, inflammation, and cancer, and has demonstrated potential medical utility in several models of toxicity. Its exact mechanism of action is poorly understood, but it has shown protection in models of vesicant toxicity including nitrogen mustard, CEES and SM[10,24,9799]. Silibinin might also reduce the nitrosative stress observed following in-vitro SM exposures through its ability to inhibit iNOS[99].…”
Section: 0 Potential Antioxidant Therapies: Mechanisms Efficacy Amentioning
confidence: 99%